High‐Density Polymer Microarrays: Identifying Synthetic Polymers that Control Human Embryonic Stem Cell Growth. Issue 6 (18th December 2013) - Hansen, Anne; Mjoseng, Heidi K.; Zhang, Rong; Kalloudis, Michail; Koutsos, Vasileios; de Sousa, Paul A.; Bradley, Mark
<x xml:space="preserve">Abstract</x> The fabrication of high‐density polymer microarray is described, allowing the simultaneous and efficient evaluation of more than 7000 different polymers in a single‐cellular‐based screen. These high‐density polymer arrays are applied in the search for synthetic substrates for hESCs culture. Up‐scaling of the identified hit polymers enables long‐term cellular cultivation and promoted successful stem‐cell maintenance. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>